2012
DOI: 10.4012/dmj.2012-209
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of hard and soft denture lining materials

Abstract: The cytotoxicity of nine soft and hard lining materials (Mollosil Plus, Ufi Gel SC, Visco-gel, Molloplast-B, GC Tissue Conditioner, Vertex Rapid Simplified, GC Reline Hard, Vertex Self-Curing, Ufi Gel hard C) was evaluated using human gingival fibroblasts (HGFs). Twelve disk samples per lining material were prepared and incubated for 24, 48, 72, and 96 h. Cytotoxicity of each lining material's extract on cultured HGFs was measured using XTT assay. Data were analyzed using one-way ANOVA, post hoc Dunnett's T3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
(29 reference statements)
1
14
0
3
Order By: Relevance
“…Although the MTT assay measures the mitochondrial metabolic activity rate as an estimate of cell viability, an observed excess of metabolic activity may also represent a response to increased cellular stress due to toxicity, thus caution is recommended with the use of MTT as its estimation of cell viability may be misleading 28 , 29 . Moreover, the MTT requires the cells to be killed, making it impossible to follow up on the cells in culture 1 , and yet requires an extended incubation time with lower sensitivity than the XTT 3 . Our experimental model designed to obtain extract media for the cell viability assay and the use of human periodontal ligament cells resembles a clinical scenario, simulating the amount and surface area of the material that usually comes in contact with surrounding tissues in most clinical applications 8 , 9 , 12 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the MTT assay measures the mitochondrial metabolic activity rate as an estimate of cell viability, an observed excess of metabolic activity may also represent a response to increased cellular stress due to toxicity, thus caution is recommended with the use of MTT as its estimation of cell viability may be misleading 28 , 29 . Moreover, the MTT requires the cells to be killed, making it impossible to follow up on the cells in culture 1 , and yet requires an extended incubation time with lower sensitivity than the XTT 3 . Our experimental model designed to obtain extract media for the cell viability assay and the use of human periodontal ligament cells resembles a clinical scenario, simulating the amount and surface area of the material that usually comes in contact with surrounding tissues in most clinical applications 8 , 9 , 12 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the increase of the thickness of the oral mucosa under the denture base is also considered a physiological response to mechanical loading [47]–[52], and no compressive forces was reproduced in this study because the plates were fixed in the molars, we may not expect any increased proliferative activity of the epithelial cells due the mechanical compression factors [49]–[52]. The histopathological changes assessed may be a response of the epithelium to the release of toxic substances [20][21], [26], [41], [52][54] and/or residual monomers [24], [31]. Despite the cytotoxicity reported in vitro [26], in this present in vivo study no histopathological changes of the epithelium were observed forlining resins tested without the application of post-polymerization heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…En düşük hücre canlılığını gösteren GC Tissue Conditioner dışında diğer tüm sert ve yumuşak astar maddelerinin biyouyumlu olduğu bildirilmiştir. 60 …”
Section: Akrilik Rezinler Ve Yumuşak Astar Materyalleriunclassified